Development of a Mathematics Multiplication Pocket as an Instructional Teaching Aid for Multiplication Concepts in Elementary School: Pengembangan Kantong Perkalian Matematika sebagai Alat peraga pada Materi Perkalian di Sekolah Dasar - Dea Windiani Windiani; Maulana Maulana; Isrok’atun Isrok’atun (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2025)
Persistent difficulties in learning multiplication at the elementary level indicate a gap between recommended use of concrete manipulatives and prevailing textbook-centered practices. This research and development (R&D) study developed Kalimatika, a low-cost concrete manipulative, and examined its feasibility and learning effectiveness for third-grade multiplication. Using the ADDIE model, six experts (three media, three content) validated the product with feasibility ratings of 94.7% and 98.6% (highly feasible). A one-group pretest–posttest implementation with 26 students yielded a mean increase from 77.15 to 92.50 and an N-Gain of 0.59 (medium). Teacher and student questionnaires indicated very good acceptance. The findings extend evidence that locally fabricated manipulatives can strengthen conceptual understanding of whole-number multiplication in elementary mathematics. Limitations include the small sample and single-group design; future work should employ controlled trials and durability improvements.